Formulation of Jackfruit Seed Protein Enriched Cake - Akter, B; Haque, MA; Ahiduzzaman, M; Haque, MA; Ali, MA (Annals of Bangladesh Agriculture, 2021)
The study was conducted to establish a formulation for development of jackfruit seed protein (JSP) enriched cake. After extracting from jackfruit seeds, the JSP flour was added as substitutions of wheat flour at a level of 0%, 3%, 6%, 8% and 10% to prepare protein enriched cakes. The cakes were then analyzed to find out the acceptable formulation by assessing their physicochemical properties and sensory attributes. The cakes prepared with 6% JSP isolate secured the maximum sensory scores in terms of color, flavor, taste, texture, and revealed the highest overall acceptability (7.58 ± 1.01) suggesting ‘like very much’. The proximate analysis of 6% JSP enriched cake showed 15.26%, 11.59%, 25.91%, 1.06%, 2.03%, and 44.15% moisture, crude protein, crude fat, ash, crude fiber, and carbohydrate respectively. An increase in JSP level in cake formulation decreased the volume, weight, specific volume and water activity while the baking loss showed a reverse trend. The JSP enriched cake also exhibited a reduction in vitamin A content and peroxide value, and an increased calorific value. Microbiological analysis of the JSP enriched cake showed an acceptable quality by 10 days of storage (25 ± 2 °C). Therefore, maximum 6% JSP flour could be added as a substitute of wheat flour to formulate a protein enriched cake having good preferences and overall acceptability. Ann. Bangladesh Agric. (2020) 24(1) : 17-39